2016
DOI: 10.1371/journal.pone.0165477
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of the Biological Responses of Canine Macrophages Challenged with PLGA Nanoparticles Containing Monophosphoryl Lipid A

Abstract: Poly (lactic-co-glycolic acid) nanoparticles (PLGA NPs) have been considerably studied as a promising biodegradable delivery system to induce effective immune responses and to improve stability, safety, and cost effectiveness of vaccines. The study aimed at evaluating early inflammatory effects and cellular safety of PLGA NPs, co-encapsulating ovalbumin (PLGA/OVA NPs), as a model antigen and the adjuvant monophosphoryl lipid A (PLGA/MPLA NPs) as an adjuvant, on primary canine macrophages. The PLGA NPs construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 33 publications
6
15
0
Order By: Relevance
“…; Guldner et al . ). Daily visual evaluation of the MoMΦ in culture for up to 5 days postviability analysis did not demonstrate cytomorphological changes that could be consistent with cell death.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…; Guldner et al . ). Daily visual evaluation of the MoMΦ in culture for up to 5 days postviability analysis did not demonstrate cytomorphological changes that could be consistent with cell death.…”
Section: Resultsmentioning
confidence: 97%
“…; Guldner et al . ). Physicochemical analysis of the PLGA/MPLA NP constructs in solution demonstrated that NPs in solution were dispersed with limited aggregation of particles.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations